2006
DOI: 10.1007/s11882-006-0063-y
|View full text |Cite
|
Sign up to set email alerts
|

Ocular toxicity of systemic asthma and allergy treatments

Abstract: Systemic medications, such as antihistaminic and anti-inflammatory agents used in the treatment of asthma and allergy, may have adverse effects on the eye. The major adverse effects on the eye have included cataracts, glaucoma, and tear-film dysfunction (dry-eye syndrome). The use of inhaled corticosteroids (bronchial and nasal) has been associated with mild systemic effects when compared with oral corticosteroids. The development of cataracts and glaucoma has been more commonly associated with earlier "hard" … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…In the eye, nose, and lung, steroids are the mainstay of regulating inflammation, but their use carries the major side effect of ocular hypertension and glaucoma 23, 24 . Resolvins are not immunosuppressant, unlike steroids or other anti-inflammatory agents currently used in the eye.…”
Section: Discussionmentioning
confidence: 99%
“…In the eye, nose, and lung, steroids are the mainstay of regulating inflammation, but their use carries the major side effect of ocular hypertension and glaucoma 23, 24 . Resolvins are not immunosuppressant, unlike steroids or other anti-inflammatory agents currently used in the eye.…”
Section: Discussionmentioning
confidence: 99%
“…For example, through a comparative analysis, Dogru et al [ 20 ] found that children with asthma have a higher rate of tear film instability, which may lead to future DED. Bielory [ 21 ] found that antihistamines and anti-inflammatory drugs used to treat asthma and allergies may exacerbate DED by causing tear film dysfunction or conjunctival overreaction. However, there are also population-based studies showing no significant association between asthma and DED.…”
Section: Discussionmentioning
confidence: 99%
“…There are a lot of date on the influence of medications (both topical and systemic) on the tear film. Some samples: ß-blockers used for glaucoma therapy reduce test Shirmer I and break-up time values, long term general anesthesia decrease basal tear production, antihistamines block both goblet cells and lacrimal glands, topical glaucoma therapy reduces LLT, oral mucolytics modify mucous layer, systemic antidepressants, anticholinergics or antihypertensives increase risk of dry eye problems [56,103,[116][117][118][119][120][121][122]. A comprehensive review of this problem with the list of medicines and herbs has been prepared by Askeroglu et al [123].…”
Section: Multilayer Disturbancesmentioning
confidence: 99%